Exploiting renewable energy opportunities through integrated regional power systems: Analysis of institutional perspectives on barriers in Southern Africa - Sichone, Elijah Chizamusoka (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPhil)--Stellenbosch University, 2018.